Adapting to climate change by water management organisations: enablers and barriers - Azhoni, Adani; Jude, Simon; Holman, Ian P. (Elsevier, 2018)
Climate change will be particularly experienced though the medium of water. Water organisations, that are managing societal and ecological needs for water, are therefore likely to experience the impact the most. This study reviews the current literature regarding adaptation to climate change by water management organisations and associated barriers. Literature on adaptive capacity is growing and a general consensus is emerging on the determinants of adaptive capacity, although variations exist regarding how it is to be evaluated, enhanced and applied to policy making due to its dynamic, contextual and latent nature. Since adaptive capacity is hard to measure and successful adaptation difficult to define, some studies focus on the existence of adaptation attributes of organisations. Studies reporting successful adaptation are minimal and barriers of adaptation are being discovered as adaptation research transitions into implementation. But the root causes of these barriers are often overlooked and the interconnectedness of the barriers is poorly addressed. Increasingly, combining top-down and bottom-up approaches to adaptation is being recommended due to the limitations of each. However, knowledge regarding how organisations operating at different scales can enhance adaptive capacity of other organisations operating at another scale is lacking due to the few studies of inter-organisational networks across scales. Social networks among actors are recognised as a key factor to enable adaptation. However, network studies generally focus on individual actors and rarely between public agencies/organisations. Moreover, the current literature is inadequate to understand the relationship between adaptation enabling characteristics, barriers and adaptation manifestation. The review demonstrates that research on understanding the emergence and sustenance of barriers is urgently required. Addressing these knowledge gaps will help to improve the design of adaptation strategies, thereby improving the ability of water management to address the ongoing challenges of climate change.
Keywords: Adaptation; Adaptive capacity; Barriers; Climate change; Inter-organisational networks; Water management organisations